PENGEMBANGAN INVESTASI WILAYAH PERBATASAN, INDUSTRI MARITIM DAN KAWASAN PERDAGANGAN BEBAS DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT PESISIR DI PROVINSI KEPULAUAN RIAU - Tumpal Manik; Henry Eryanto; Lia Suprihartini (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2017)
The purpose of this research to create the boder region of investment development model, the maritime industry investment development model and Free Trade Zone development model effect on increase the welfare of coastal communities.The research location is in the of Riau Islands Province at Batam, Bintan and Karimun in 2016 with 200 research data. Analysis of the research through modeling path diagram, goodness of fit test (GOF) and the test results prove that the model evaluation through feasibility test models of assessment criteria Goodness of Fit (GOF) proved to be a model drawn up by researchers is the model has fit so that the model is said to fit the observed data development investment has met the criteria GOF through the test. Analysis of the research through modeling path diagram, goodness of fit test (GOF) and the test results prove that the model evaluation through feasibility studies Goodness of Fit (GOF) proven models arranged by researchers is the model has fit so that the model is said to fit the observed data to develop investment meets the criteria GOF through Chi-square test, probability of> 0.05, CMIN / DF≤2,00, RMSEA≤0,08, GFI≥0,90, AGFI≥0,90, TLI≥0,90, NFI≥0,90, CFI≥ 0.95. The results of the research hypotheses prove that the investment development of boder region, maritime industry and Free Trade Zone significant effect on increase the welfare of coastal communities in Riau Islands Province at Batam, Bintan and Karimun.